The Nehari manifold for a Kirchhoff type problem involving sign-changing weight functions - Chen, Ching-yu; Kuo, Yueh-cheng; Wu, Tsung-fang (Journal of Differential Equations, 2011)
This paper examines a class of Kirchhoff type equations that involve sign-changing weight functions. Using Nehari manifold and fibering map, the existence of multiple positive solutions is established.